Evaluation of the trace element concentration in some livestock and poultry bone samples using X-ray fluorescence - Dler Aladdin; Asaad H. Ismail; Akram H. Taha; Zakariya A. Hussein (Zanco Journal of Pure and Applied Sciences, 2022)
Element concentration (ppm) in some samples of livestock and poultry animals' bones haven evaluated using X-ray fluorescence (XRF) technique. The study included evaluation of the concentration of more than 20 elements in bone samples It has focused on the impacts of freezing process on the concentration of elements The results demonstrated that the element concentrations were reduced by freezing samples. The higher effects were on the concentration of (Cr, Al, Zn, Sr, Mg, K, Ca, Cu, Fe, S, and P) for the bones of cow and sheep, and the most effects were in cow's bone samples. Maximum and minimum ratio value element concentration (cow and sheep livestock samples/ cow and sheep freezing samples) were 54.5 ± 12.2 ppm (element of Cr) and 0 ppm (element of Ba, Mn, Ti, Sn, and Rb), respectively. The results of element concentration in chicken bone samples indicated that the high element concentration was in bone samples of livestock chicken (organic) compared with the poultry chicken (fresh and freezing). XRF, Bone, Livestock, Poultry, Trace elements, freezing meat,